MOTIVASI MAHASISWA PRODI S1 KEPERAWATAN DALAM MENGERJAKAN SKRIPSI DI STIKES BINA SEHAT PPNI MOJOKERTO - triwibowo, Heri; Frilasari, Heni (JURNAL KEPERAWATAN SEHAT, 2013)
Thesis is a scientific work that is required as a part of the requirements of academic education in auniversity. In making thesis, students must have a good motivation that the thesis can be done well anyway.Meanwhile, the motivation is based on the internal needs that drive and control the behavior of individuals. Thegoal of this research is to determine the motivation of the students of Prodi S1 Nursing in working on thesis inacademic year 2011-2012 at StikesBinaSehat PPNI Mojokerto. Its population consisted of 85 students withpurposive sampling technique obtained 67 students as samples. Variable in the study was motivation of thestudents of Prodi S1 nursing StikesBinaSehat PPNI Mojokerto who were in VIII semesters. The result showedthe greatest percentage is 64,2% which lies in the group of respondents who have medium motivation to finishthesis as many as 43 respondents. Some resistance in the common mistakes that often occur among students in theprocess of writing the final lecture (thesis), especially on program S1 is as follows: errors in the formulation of aresearch study, errors in library search, errors in process of collection reseacrh data, errors in using standardmeasuring instrument, errors in the application of statistical tools, errors in preparing the study design andmethodology, errors in data collection techniques, errors in applications of research method. Thesis workprocess is not so simple as imagine so it requires a lot of effort and sacrifice that does not little to complete thethesis, for this students are expected to be more independent, active and able to think scientifically. It isinfluenced by several factors such as lack of support from the closest people to such as parents, friends andlecturers so the lack of students to get assistance, criticism, advice and input whendealingwithproblemsinworkingonthethesis.Keywords: Motivation, Students, Thesis